Transformasi Literasi Digital dan Pendidikan Karakter Moderat Melalui Ghazalia Collage - Rima Ronika; Fina Ulya (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2025)
The development of digital technology affects all aspects of human life, one of the characteristics of which is the overflow of information without any filter, this is the cause of the birth of hoaxes, slander and hate speech. To overcome this flood of information, media were born that carry a mission of friendliness and peace, one of which is Ghazalia Collage. In the midst of the spread of various Islamic content, Ghazalia Collage has its own distinction, namely studying Al Ghazali's works using the Islamic boarding school model. This article will discuss the method of studying Sufism at Ghazalia College and the responses of online students to this study. This research employs a virtual ethnography method to examine digital interactions, practices, and meanings within online spaces in order to analyze this question using Dennis McQuail’s theory. The main elements of the theory: a. Message (stimulus) b. A receiver or receiver c. Effect (response). Urban communities are Ghazalia Collage's audience, so the choice of diction and explanations are adapted to the language style commonly used by urban communities. Apart from that, the research explains that Al-Ghazali’s Sufism serves as the fundamental basis for moderate character education. Furthermore, the understanding of Al-Ghazali’s texts is integrated with other disciplines, such as the social sciences